Improved antiparasitic activity by incorporation of organosilane entities into half-sandwich ruthenium(ii) and rhodium(iii) thiosemicarbazone complexes1. Issue 5 (7th February 2015) - Adams, Muneebah; de Kock, Carmen; Smith, Peter J.; Land, Kirkwood M.; Liu, Nicole; Hopper, Melissa; Hsiao, Allyson; Burgoyne, Andrew R.; Stringer, Tameryn; Meyer, Mervin; Wiesner, Lubbe; Chibale, Kelly; et al.
<x xml:space="preserve">Abstract</x> Ferrocenyl- and aryl-functionalised organosilane thiosemicarbazones.